Repair of Composites and Sandwich Structures - Marcelo F. S. F. de Moura (2008)
The repair of composites and sandwich structures is studied experimentally and numerically. Repair is fundamental to avoid premature replacement of damaged components. Efficient predictive numerical tools of the mechanical behaviour of repaired structures are necessary to increase the confidence of designers. In this context, cohesive damage models have acquired special relevancy owing to their capacity to simulate damage onset and growth. A mixed-mode cohesive damage model based on interface finite elements and accounting for ductile behaviour of adhesives is presented. The cohesive parameters of the constitutive softening laws are determined using an inverse method applied to fracture characterization tests under pure modes I and II. A new data reduction scheme based on crack equivalent concept is applied in the fracture characterization tests. The cohesive laws are used to predict the mechanical behaviour of scarf repairs of composites and sandwiches. Good agreement was found between experimental and numerical results, for strength versus scarf angle, showing that the proposed model can be successfully applied to bonded repairs.